Calidad de atención de enfermería y estancia hospitalaria en neonatos prematuros Hospital Belén de Trujillo - Arista Montes, Maria de los Angeles (2020)
The present investigation was carried out; in order to determine the relationship between the quality of nursing care and hospital stay in premature infants. The sample consisted of 40 nurses, who met the established inclusion criteria, and the hospitalized neonates' admission and discharge records book making a total of 40. For data collection, the checklist of quality of care was used. Nurse's care and the data collection sheet for the hospital stay of the premature newborn. The information obtained is presented in simple tables and double entry. For statistical analysis, the Chi Square statistical test was used. At the conclusion of the analysis, it was determined that the quality of care provided by the 40 nurses in the dimensions: structure, was regular with 62.5%; good 37.5%; in the process, good with 92.5%, poor 7.5%, and result, being good 95%. Likewise, of the total of premature infants, it was obtained that 75% had a short hospital stay, and a prolonged one, reaching only 25%. In conclusion, that it is significantly related to the hospital stay of the premature neonate with respect to the structural dimension p = 0.035; process dimension: p = 0.008 and result dimension: p = 0.015.